Low-Complexity Linear Equalization for OTFS Modulation - Surabhi, G. D.; Chockalingam, A. (IEEE communications letters, 2020)
In this letter, we propose low-complexity linear equalizers for orthogonal time frequency space (OTFS) modulation that exploit the structure of the effective channel matrix in OTFS. The proposed approach exploits the block circulant nature of the OTFS channel matrix to achieve significant complexity reduction. For an N × M OTFS system, where N and M are the number of Doppler and delay bins, respectively, the proposed approach gives exact minimum mean square error (MMSE) and zero-forcing (ZF) solutions with just O(MN log MN) complexity, while MMSE and ZF solutions using the traditional matrix inversion approach require O(M 3 N 3 ) complexity. The proposed approach can provide low complexity initial solutions for local search techniques to achieve enhanced bit error performance.